Large scale slope stability in open pit mining : a review - Sjöberg, Jonny (Luleå tekniska universitet, Geoteknologi, 1996)
Design of open pit slope angles is becoming more and more important as the mining depths of open pits continuously increase. Small changes in the overall pit slope angle have large consequences on the overall economy of the mining operation. A case in particular is the Aitik open pit mine in northern Sweden, which currently faces the design of the overall slope angles for continued mining toward a depth of around 500 meters. This report constitutes the first phase in a research project aimed at developing design methods for large scale pit slopes. In this report, the stability and design of large scale pit slopes in open pit mining is reviewed, with special reference to slopes in hard, jointed, rocks, similar to the rock types found at the Aitik mine. The review covers the mechanics of pit slopes, existing design methods for large scale slopes, remedial measures and mining strategy to cope with slope failures, and a compilation of case studies from open pits worldwide. Finally, suggestions for future research in this area are presented. The factors governing large scale slope stability are primarily: (1) the stress conditions in the pit slopes, including the effects of groundwater, (2) the geological structure, in particular the presence of large scale features, (3) the pit geometry, and (4) the rock mass strength. Observed failure modes in rock slopes are of a wide variety. On a bench scale, structurally controlled failures such as plane shear and wedge failures are common. However, as the scale increases, simple structurally controlled failures are less dominate, and more complex failures such as step-path failures start to develop. From observations, it appears that for large scale slopes, two failure modes are especially important to consider. These are (1) rotational shear failure, and (2) large scale toppling failure. Rotational shear failure in a large scale slope involves failure both along pre-existing discontinuities and through intact rock bridges, but where the overall failure surface follows a ...